ENHANCING THE DATA SECURITY IN CLOUD COMPUTING BY USING NEW ENCRYPTION METHOD - Ahmed, Farah Qasim Ahmed; Amin Salih Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
With the huge growth of the critical data that saved in the cloud, the security of the cloud should be safer. The growing of the cloud users attended with the rising of the harmful attacks and natural processes. Many weaknesses and security advisories are discovered. The idea of using the cloud is not considered as a new term but was traded widely these days with the improvement of business and general investments, which completely depends on internet services in executing the work with accuracy and professionally. This paper proposed a new encryption technique that protects the data before it is saved to cloud services and retrieved, hence the confidentiality of the data can be secured. Also, this paper compares proposed method (3xAES) with AES and T-DES algorithms by calculating the key generation, encryption and decryption time for each algorithm. 3×AES technique is more efficient and secured, more than AES because it encrypts the text 3 times and each time it needs a different key for encrypt and decrypt. Comparing between 3×AES with AES and T-DES and the result was that 3×AES has a higher security than AES and 3DES, due to the triple encryption for the 3×AES algorithm. By increasing the key length, the higher security will occur, so the algorithm 3×AES with the key length 256, will put in advance over AES and 3-DES for securing the data that save on the cloud computing.